Bergey's Manual of Systematics of Archaea and Bacteria 2015
DOI: 10.1002/9781118960608.gbm00148
|View full text |Cite
|
Sign up to set email alerts
|

Micromonospora

Abstract: Mi.cro.mo.no.spo'ra. Gr. adj. mikros small; Gr. adj. monos single, solitary; Gr. fem. n. spora a seed and in biology a spore; N.L. fem. n. Micromonospora small, single‐spored (organism). Actinobacteria / Actinobacteria / Micromonosporales / Micromonosporaceae / Micromonospora Well‐developed, branched, substrate mycelium (0.2–0.6 µm diameter). Nonmotile spores are borne sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…The genus Micromonospora represented by Gram-stain positive, filamentous and sporulating actinobacteria, belongs to the family Micromonosporaceae of the order Micromonosporales in the phylum Actinobacteria (Genilloud, 2015a , b , c ). The type species of the genus is Micromonospora chalcea and currently includes 81 species with validly published names http://www.bacterio.net/micromonospora.html (Parte, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Micromonospora represented by Gram-stain positive, filamentous and sporulating actinobacteria, belongs to the family Micromonosporaceae of the order Micromonosporales in the phylum Actinobacteria (Genilloud, 2015a , b , c ). The type species of the genus is Micromonospora chalcea and currently includes 81 species with validly published names http://www.bacterio.net/micromonospora.html (Parte, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, almost half of actinobacteria (46%) were identified as Micromonospora . Members of this genus have been isolated from various habitats including plants ( Trujillo et al, 2010 , 2015 ; Carro et al, 2012 , 2013 ; Genilloud, 2015 ). Several new species of Micromonospora are endophytes of various plants as exemplified by the description of M. costi ( Thawai, 2015 ), M. globbae ( Kuncharoen et al, 2018 ), M. phytophila ( Carro et al, 2018b ), M. luteiviridis ( Carro et al, 2018b ), M. oryzae ( Kittiwongwattana et al, 2015 ), and M. terminaliae ( Kaewkla et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Micromonospora , class Actinobacteria , contained over 80 validly described species (1) at the time of writing. Although several species have terrestrial origin, they have also been associated with marine environments (2), sea sands (3), near-shore sediments (4), deep-sea sediments (5, 6), and marine sponges (7). Micromonospora spp.…”
Section: Announcementmentioning
confidence: 99%
“…Micromonosporae show 16S rRNA similarity values within the range of 96.7% to 99% (2), making the description of putative novel species difficult without full-genome sequences. Micromonosporae have also been found to be a promising source of biosynthetic metabolites (9).…”
Section: Announcementmentioning
confidence: 99%